Hydrogeological Classification and the Correlation of Groundwater Chemistry with Basin Flow in the South-Western Part of Bangladesh - Dola, Shahpara Sheikh; Bahsar, Khairul; Islam, Mazeda; Sarker, Md Mizanur Rahman (Journal of Bangladesh Academy of Sciences, 2018)
Attempt has been made to find the relationship between the basin groundwater flow and the current water chemistry of south-western part of Bangladesh considering their lithological distribution and aquifer condition. The correlation of water chemistry and basin groundwater flow is depicted in the conceptual model. The water-types of shallow groundwater are predominantly Mg-Na-HCO3 and Ca- Mg-Na-HCO3 type. In the deep aquifer of upper delta plain is predominately Na-Cl, Ca-HCO3 and Mg- HCO3 type. In the lower delta plain Na-Cl type of water mainly occurs in the shallow aquifer and occasionally Ca-HCO3, Ca-Mg-Na-HCO3 and Mg-HCO3 type may also occur in shallow aquifer of the eastern part of lower delta plain which could have originated from the recent recharge of rain water. Na- Cl type water is also found in the deep aquifer of lower delta plain. The origin of Na-Cl type water in the deep aquifer of lower delta part might be connate water or present day sea water intrusion. Fresh water occurring in the deep aquifer in the lower delta area is mostly of Mg-Ca-HCO3 and Na-HClO3 types. This type of water originate from intermediate or deep basin flow from the northern part of Bangladesh. The probable source of deep groundwater is Holocene marine transgression (Khan et al. 2000) occurred in 3000–7000 cal years BP and the deep groundwater of Upper Delta plain and Lower Delta plain is clearly influenced by deep basin flow coming from north part of Bangladesh Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 41-54, 2018